The anthropology of economy : community, market, and culture - Gudeman, Stephen (Blackwell, 2001)
"This book illustrates that, across cultures, economy can be understood as a combination of both community and market forces. Drawing from the work of anthropologists, as well as that of economists, sociologists, historians, geographers, feminists, and post-Marxists, Gudeman presents an anthropological approach to economy that highlights the centrality of communal processes in the market.